Identification and characterization of a novel ferric reductase from the hyperthermophilic Archaeon Archaeoglobus fulgidus - Vadas, A; Monbouquette, H G; Johnson, E; Schröder, I (The Journal of biological chemistry, 1999)
Archaeoglobus fulgidus, a hyperthermophilic sulfate-reducing Archaeon, contains high Fe(3+)-EDTA reductase activity in its soluble protein fraction. The corresponding enzyme, which constitutes about 0.75% of the soluble protein, was purified 175-fold to homogeneity. Based on SDS-polyacrylamide gel electrophoresis, the ferric reductase consists of a single subunit with a M(r) of 18,000. The M(r) of the native enzyme was determined by size exclusion chromatography to be 40,000 suggesting that the native ferric reductase is a homodimer. The enzyme uses both NADH and NADPH as electron donors to reduce Fe(3+)-EDTA. Other Fe(3+) complexes and dichlorophenolindophenol serve as alternative electron acceptors, but uncomplexed Fe(3+) is not utilized. The purified enzyme strictly requires FMN or FAD as a catalytic intermediate for Fe(3+) reduction. Ferric reductase also reduces FMN and FAD, but not riboflavin, with NAD(P)H which classifies the enzyme as a NAD(P)H:flavin oxidoreductase. The enzyme exhibits a temperature optimum of 88 degrees C. When incubated at 85 degrees C, the enzyme activity half-life was 2 h. N-terminal sequence analysis of the purified ferric reductase resulted in the identification of the hypothetical gene, AF0830, of the A. fulgidus genomic sequence. The A. fulgidus ferric reductase shares amino acid sequence similarity with a family of NAD(P)H:FMN oxidoreductases but not with any ferric reductases suggesting that the A. fulgidus ferric reductase is a novel enzyme.